Population Distribution Information System in Tugumulyo District - Ahmad Syazili; Ahmad Mutatkin Bakti (Universitas Bina Darma, 2020)
Information on population data is quite important information for stakeholders. Information on population data is often used in various ways such as aiding, or government activities related to population data. The information that is often needed is related to the actual existence of the population in order to conduct a census or other social interests. For this reason, in this study the development of a population mapping information system in Tugumulyo sub-district was made as an effort to provide information to the public regarding population data. In the process of developing information systems, web engineering development methods are used. Web engineering method is a method used to develop a web-based information system. The results of the development in the form of a population distribution information system with the main features of population data information are presented in the form of tables, graphics and maps. In addition, the information displayed can be seen based on the sub-district and also the village or village in the sub-district